Regional integration policies and ecological resilience: a case study of urban agglomeration planning policies in China - Li, Yuanzhu; Pan, Zhongfeng; Shen, Yang (Frontiers in Environmental Science, 2025)
Facing the severe challenges of global climate change, cities must transition to regenerative, equitable, and adaptive systems, which serves as the cornerstone of urban sustainable development. This study employs a multi-period difference-in-differences approach as a quasi-natural experiment to investigate how regional integration policies (RIP) shape urban ecological resilience (UER), with a particular concentration on the underlying mechanisms. The findings demonstrate that Regional integration significantly enhances urban ecological resilience. Heterogeneity analysis reveals that RIP exerts a pronounced positive effect on UER in eastern cities, whereas its impact is statistically insignificant in central and western regions. Moreover, the policy exerts a substantially stronger influence on provincial capitals compared to non-capital cities. RIP affects UER primarily through industrial structure upgrading and technological innovation. These analysis demonstrate the critical role of inter-city interactions and interdependencies in cross-administrative ecological governance, providing a scientific foundation for optimizing regional governance frameworks and enhancing ecological security.